2024
DOI: 10.3897/pharmacia.555.e113097
|View full text |Cite
|
Sign up to set email alerts
|

Novel anticoagulants in the management of atrial fibrillation: A comprehensive comparative analysis

Mazen M. Jwaid,
Mohammed J. Alwan,
Isam Ihsan
et al.

Abstract: Background: Atrial fibrillation (AF) stands as the most prevalent cardiac arrhythmia, with associated risks of stroke and systemic thromboembolism. While vitamin K antagonists, specifically warfarin, have historically been the mainstay for stroke prevention in AF, they come with inherent limitations. Aim: This review seeks to offer a comprehensive analysis of the efficacy, safety, and clinical advantages of novel oral anticoagulants (NOACs) compared to traditional warfarin in AF management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…One class of novel anticoagulant agents that has garnered attention in HF management is the DOACs. DOACs, including dabigatran, rivaroxaban, apixaban, and edoxaban, selectively inhibit key factors in the coagulation cascade, such as thrombin or factor Xa, thereby preventing thrombus formation [23][24][25]. Clinical trials evaluating the efficacy and safety of DOACs in HF patients with AF have demonstrated comparable or superior efficacy in reducing stroke and systemic embolism compared to warfarin, with lower rates of intracranial bleeding [26,27].…”
Section: Novel Anticoagulant Agents and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…One class of novel anticoagulant agents that has garnered attention in HF management is the DOACs. DOACs, including dabigatran, rivaroxaban, apixaban, and edoxaban, selectively inhibit key factors in the coagulation cascade, such as thrombin or factor Xa, thereby preventing thrombus formation [23][24][25]. Clinical trials evaluating the efficacy and safety of DOACs in HF patients with AF have demonstrated comparable or superior efficacy in reducing stroke and systemic embolism compared to warfarin, with lower rates of intracranial bleeding [26,27].…”
Section: Novel Anticoagulant Agents and Future Perspectivesmentioning
confidence: 99%
“…Furthermore, novel anticoagulant agents targeting alternative pathways in the coagulation cascade, such as factor XI inhibitors, are currently under investigation and may offer additional therapeutic options for HF patients [28,29]. These agents have the potential to provide effective thromboprophylaxis while minimizing bleeding risk, particularly in high-risk patient populations where traditional anticoagulants may be less tolerated or contraindicated [23][24][25][26][27].…”
Section: Novel Anticoagulant Agents and Future Perspectivesmentioning
confidence: 99%